A Prediction Model for Severe Maternal Morbidity in Laboring Patients at Term - Rosenbloom, Joshua I.; Tuuli, Methodius G.; Stout, Molly J.; Young, Omar M.; Woolfolk, Candice L.; López, Julia D.; Macones, George A.; Cahill, Alison G. (American Journal of Perinatology, 2019)
Objective To determine the factors associated with severe maternal morbidity in a modern cohort of women laboring at term and to create a prediction model.Study Design This is a retrospective cohort study of all term, laboring patients with live births at a single tertiary care center from 2004 to 2014. The primary outcome was composite maternal morbidity including organ failure, amniotic fluid embolism, anesthesia complications, sepsis, shock, thrombotic events, transfusion, or hysterectomy. Multivariable logistic regression was used to identify independent risk factors. Antepartum, intrapartum, and combined risk scores were created and test characteristics were analyzed.Results Among 19,249 women delivering during the study period, 323 (1.68%) patients experienced severe morbidity, with blood transfusion the most common complication (286, 1.49%). Factors in the antepartum model included advanced maternal age, race, hypertension, nulliparity, history of cesarean delivery, smoking, and unfavorable Bishop score. Intrapartum factors included mode of delivery, use of cervical ripening agents or oxytocin, prolonged second stage, and macrosomia. The combined model had an area under the curve of 0.76 (95% confidence interval [CI], 0.73, 0.79).Conclusion This three-part risk scoring system can help clinicians counsel patients and guide clinical decision making for anticipating severe maternal morbidity and necessary resources.
Keywords: maternal morbidity; labor; risk score; outcome prediction